FROM PEOPLE'S DIALOGUE TO SCHOOL SPEECH: DEVELOPING ORAL SKILLS (International journal of artificial intelligence, 2026)
This article examines the influence of the national language environment and dialectal characteristics on the development of schoolchildren's oral speech. Particular attention is paid to dialectal vocabulary and pronunciation as elements of folk culture and factors influencing adherence to the norms of modern Russian literary language. Methods for developing dialogic, spontaneous speech are analyzed, including a system of communicative exercises, practice dialogues, and situational microdialogues. It is shown that organizing learning situations that mimic real-life communication fosters spontaneous, proactive, and creative speech in students. The importance of combining the development of speech skills and abilities with the use of stimuli and questions to stimulate students' speech activity is emphasized. The influence of modern sources of linguistic material, including online discourse, is also considered as a factor in the development of new communication models.